The impact of augmented reality learning experiences based on the motivational design model: A meta-analysis - Prasetya, Febri; Fortuna, Aprilla; Samala, Agariadne Dwinggo; Rawas, Soha; Mystakidis, Stylianos; Syahril; Waskito; Primawati; Wulansari, Rizky Ema; Kassymova, Gulzhaina Kuralbayevna (Social sciences & humanities open, 2024)
This meta-analysis examined the impact of augmented reality learning experiences on the motivational design model to obtain findings related to student attention, material relevance, increased confidence, and student satisfaction; however, heterogeneity in the sample population of this study was ignored. The analysis utilized Preferred Reporting Items for Systematic Reviews and meta-analysis guidelines to logically define and communicate outcomes, employing JASP software for quantitative study and VOSviewer to visualize tendencies and connections amid bibliometric examination to recognize gaps in sources. The exploration incorporated twenty-five comparative analyses evaluating how interventions affected student enthusiasm. Encouraging effects were noticed, specifically in concentration attention (dRe = 0.816), relevance (dRe = 0.787), confidence (dRe = 0.773), and satisfaction (dRe = 0.787). Furthermore, subsequent identification of possible publication bias through Egger’s test and funnel plot revealed no issues of publication bias in this meta-analysis study. The study concluded that learners showed that the four design models had more positive motivation towards augmented reality learning than those who did not engage in augmented reality-based learning. Nevertheless, some studies included in this meta-analysis had minuscule sample sizes and short intervention durations. Future research efforts should encompass extended interventions and implementations, delving into augmented reality learning through empirical studies to achieve a more expansive influence and diverse representation of student groups.